Antibiotic-based small molecular micelles combined with photodynamic therapy for bacterial infections - Lijiao Yang; Shaomin Song; Meihui Yin; Min Yang; Daoping Yan; Xiaohui Wan; Jipeng Xiao; Yuchen Jiang; Yongchao Yao; Jianbin Luo (Elsevier, 2023)
The appearance of multidrug-resistant bacteria and the formation of bacterial biofilms have necessitated the development of alternative antimicrobial therapeutics. Antibiotics conjugated with or embedded in nano-drug carriers show a great potential and advantage over free drugs, but the mass proportion of carriers generally exceeds 90% of the nano-drug, resulting in low drug loading and limited therapeutic output. Herein, we fabricated a nanocarrier using antibiotics as the building blocks, minimizing the use of carrier materials, significantly increasing the drug loading content and treatment effect. Firstly, we conjugated betaine carboxylate with ciprofloxacin (CIP) through an ester bond to form the amphiphilic conjugate (CIP-CB), which self-assembled into micelles (CIP-CBMs) in aqueous solutions, with a CIP loading content as high as 65.4% and pH-induced surface charge reversal properties. Secondly, a model photosensitizer (5, 10, 15, 20-tetraphenylporphyrin (TPP)) was encapsulated in CIP-CBMs, generating infection-targeted photodynamic/antibiotic combined nanomedicines (denoted as TPP@CIP-CBMs). Upon accumulation at infection sites or in deep bacterial biofilms, the ester bond between the betaine carboxylate and CIP is cleaved to release free TPP and CIP, leading to a synergetic antibacterial and antibiofilm activity in vitro and in vivo.